Pengaruh Penambahan Enhancer Isopropil Miristat dan dan Propilen Glikol terhadap Penetrasi Krim Asiklovir - Estu Mahanani Dhilasari (UIN Syarif Hidayatullah Jakarta, 2022)
Acyclovir, a BCS class III drug, has a high ability to fight the herpes virus but has low permeability and is poorly soluble in water. In order to obtain the expected effect of viral infection on the skin, the penetration of the active ingredients becomes a critical factor for a topical treatment to achieve the desired concentration. This study was to see the effect of adding isopropyl myristate and propylene glycol as enhancers that help diffuse the drug through the stratum corneum. The formulation is made by adding enhancer propylene glycol 8% (F1), isopropyl myristate 8% (F2), and without enhancers (F3). Physical stability of acyclovir cream, including homogeneity, organoleptic, pH, viscosity, type of emulsion and power spread, and in vitro cream penetration test with Franz diffusion cells will be observed. The result of acyclovir cream preparations F1, F2, and F3 had a homogeneous preparation of white semisolid and odorless with pH between 7,30-7,60, emulsion type o/w, and a viscosity between 35000-47000 cPS. The cumulative amount of acyclovir penetrated at F3 was 226,008± 8,462 μg/cm2, while the cream containing the enhancers F1 258,059±1,730 μg/cm2 and F2 268,336±0,740 μg/cm2, respectively. The presence of enhancers will increase the penetration ability of acyclovir cream, with more penetration using isopropyl myristate than propylene glycol.